2022
DOI: 10.1155/2022/2814216
|View full text |Cite
|
Sign up to set email alerts
|

UI Design and Optimization Method for Museum Display Based on User Behavior Recommendation

Abstract: In view of the lack of rich display methods in the display design of museums, it is impossible to enhance the interest of visitors. This paper proposes a museum object recommendation method based on collaborative filtering, which simplifies the display design, improves the recommendation effect, and alleviates the scalability problem. Firstly, the algorithm of recommendation system combines the advantages of memory collaborative filtering and uses smoothing processing to improve the efficiency of recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…The methodology has been verified using a testbed connected to a virtual machine system hosted at Cetraro's "Museum of the Bruttians and the Sea" (Italy). The research [10] suggested a collaborative filtering-based strategy for recommending museum objects that makes display design simpler, enhances the effectiveness of recommendations, and solves the scalability issue. To increase the effectiveness of recommendations and achieve the highest level of consistency, the recommendation system's algorithm combines the benefits of memory collaborative filtering with smoothing processing.…”
Section: Related Workmentioning
confidence: 99%
“…The methodology has been verified using a testbed connected to a virtual machine system hosted at Cetraro's "Museum of the Bruttians and the Sea" (Italy). The research [10] suggested a collaborative filtering-based strategy for recommending museum objects that makes display design simpler, enhances the effectiveness of recommendations, and solves the scalability issue. To increase the effectiveness of recommendations and achieve the highest level of consistency, the recommendation system's algorithm combines the benefits of memory collaborative filtering with smoothing processing.…”
Section: Related Workmentioning
confidence: 99%